A pilot study of social and structural determinants of health (SSDOH) measures in an Alzheimer's Disease Research Center (ADRC) cohort. Issue 10 (31st December 2021) - Midgett, Sharnita; Mechanic‐Hamilton, Dawn; Karlawish, Jason; Wolk, David A; Stites, Shana Dh
Abstract: Background: Research shows that people have different experiences, opportunities, and challenges depending on their background and life circumstances. These circumstances can be important social and structural determinants of health (SSDoH) that may help explain heterogeneity in cognitive, functional, and interventional outcomes in Alzheimer's disease and related dementias (ADRDs). The National Institute on Aging has set as a priority understanding the effects of SSDoH. This information may help elucidate disease mechanisms and modifiers as well as aid discovery of disease modifying treatments that are effective across diverse populations. Method: A battery of SSDoH measures was constructed based on instrument content relevance and psychometric properties. The battery is being pilot tested in a diverse cohort of older adults. We will report the results of that pilot testing. The battery consists of self‐report measures in 6 categories: (1) Education: highest grade or academic level completed, (2) Occupation: o ccupational cognitive requirements score (OCRS) and occupation description, (3) Economic Status and Strain: financial strain (2‐item mean index), total economic problems (7‐item inventory, range: 0–7) and Agency for Healthcare Research and Quality (AHRQ) socioeconomic status index, (4) Subjective Stress: Everyday Discrimination Scale (EDS), Perceived Stress Scale (PSS), self‐report primary caretaker well‐being, and the Social Deprivation Index (SDI), (5) Early Life Stressors: parental stressors (3‐item mean index), parental educational involvement (2‐item mean index), hunger (1 item), and parental/caregiver education, occupation and health status during participant's childhood (3 items), (6) Subjective Social Support and Status: Social Network Index (SNI) and the MacArthur Scale of Subjective Social Status. Sociodemographic data collected includes self‐report of age, race, and sex, orientation, gender and identity (SOGI) questions. Collection of race data is based on National Institutes of Health (NIH) standards. Result: We describe the results of pilot testing of SSDoH measures in the Penn ADRC UDS cohort, including return rates, participant experience, and other measures of feasibility and usefulness. Conclusion: We discuss the feasibility of routinely collecting SSDoH data in an ADRC research cohort. We describe factors to consider when selecting modules to implement in standing cohorts and options for adapting the SSDoH module‐based battery to a range of research cohorts.